Dari Teodisi dan Antropodisi Menuju Teo-antropodisi: Mengasihi Allah dan Sesama di Tengah Pandemi COVID-19 - Fangidae, Tony Wiyaret (Sekolah Tinggi Teologi SAAT, 2020)
From Theodicy and Anthropodicy to Theo-anthropodicy: Loving God and Loving Others Amid the COVID-19 Pandemic. Suffering is an inevitable reality. This time, the world is dealing with a COVID-19 pandemic that causes suffering in several aspects of human life such as health, social, economic, psychological, and religion. This polemic leads us to a discussion around theodicy. Theodicy is a paradigm Leibniz used to defend God's benevolence and omnipotence in front of the reality of suffering, but the theories tend to stop in the realm of theory without practice. Sontag carries the paradigm of anthropodicy in the form of social solidarity that promotes the practice of criticizing the overly abstract theodicy in defense of God regardless of human suffering. Anthropodicy seems to be too socialist and tends to hold on to human abilities, thus excluding the religious aspect in social solidarity. Levinas responded to this anxiety by carrying an ethical theodicy. The ethical theodicy paradigm is used by Levinas to demonstrate God's presence through humans who took responsibility for alleviating the suffering of his neighbor. This article proposes a new name, meaning, and development of ethical theodicy, namely theo-anthropodicy. Theo-anthropodicy is a paradigm that embraces both theodicy as well as anthropodicy. Theo-anthropodicy seeks to prove God's love neither with Leibniz-style defenses that merely theorize nor with Sontag-style social solidarity that merely promotes practices. Theo-anthropodicy correlates these theories and practices in the same way that faith (theodicy), without action (anthropodicy) is dead. Theo-anthropodicy is Â based on the principles of